The Bombing of Afghanistan: The Convergence of Media and Political Power to Reduce Outrage - Brendan Riddick (Revista de Paz y Conflictos, 2012)
The United States (US)-led war in Afghanistan has resulted in high levels of civilian casualties and human suffering for over nine years. One of the primary causes of this suffering during the first three months of the war came from high altitude bombing led by the US Air Force. Tens of thousands of bombs equal to approximately 14,000 tons were used over Afghanistan in the first three months of the war from October 2001. However the damaging effects of this bombing campaign were largely hidden from Western audiences. This article examines techniques used by the US government and two mainstream media organisations to alter perceptions of the early stages of the air war in order to dampen indignation over the injustice being perpetrated against Afghanistan's civilian population. These techniques can be organised under five headings: coverup, devaluation, reinterpretation, the use of official channels and intimidation.